The cuban radio against the COVID-19. A case study - Beatriz Elena Fonseca Muñoz (Universidad Carlos III de Madrid, 2020)
The presence of the new coronavirus since December 2019 has transformed life dynamics worldwide. In their multi-sectoral confrontation, the communication processes that take place in all media, including radio, also intervene. To characterize how communication about COVID-19 is done in the musical programming of the Radio Progreso station is the objective of this work. A content analysis is applied to two radio music programs to show how to use the expressive resources of the medium and the format to do so. It is verified that both the radio spots and the interventions of broadcasters, specialists and guests agreed on the orientation and sensitization of citizens to assume a responsible attitude in order to overcome the health crisis. These communication actions consolidate the communication and health binomial into a recreational / educational variant, in order to overcome the current pandemic.